Screening for hemodialysis graft stenosis and short-term thrombosis risk: A comparison of the available tools. Issue 2 (March 2020) - Tessitore, Nicola; Lipari, Giovanni; Contro, Alberto; Moretti, Francesca; Mansueto, Giancarlo; Poli, Albino
Introduction: Guidelines recommend hemodialysis graft screening to identify and repair significant (>50%) stenosis at high risk of thrombosis, but there is insufficient evidence to prefer one or other screening tool due to the lack of studies comparing all available options. Methods: Seeking an optimal screening approach, we compared the performance of all currently used tools (duplex ultrasound to detect significant stenosis (StD) and measure access blood flow (QaD), ultrasound dilution access blood flow (QaU), static venous intra-access pressure ratio (VAPR), dynamic arterial and venous pressures measurement, and monitoring) for diagnosing significant angiography-proven stenosis (StA) and predicting incipient thrombosis (occurring within 4 months) in 62 grafts. All thrombotic and symptomatic acute hypotension episodes were recorded during follow-up. Results: VAPR > 0.70 and QaU < 1600 mL/min were the best indicators to angiography for those aiming to identify the majority of StA (91% sensitivity) and QaU < 1000 mL/min or StD for those aiming to avoid unnecessary angiograms (95%–93% positive predictive value). At Cox's analysis, the only significant thrombosis predictors were acute hypotension episodes (relative risk = 4.4 (95% confidence interval = 2.2–8.8), p < 0.0001) and QaU or QaD (14% (95% confidence interval = 8–21) or 16% (95% confidence interval = 6–25) increased risk per 100 mL/min drop in Qa, p < 0.003). Thrombosis risk (adjusted for acute hypotension) became significantly higher at QaU = 1000–700 mL/min (relative risk = 3.6 (95% confidence interval = 1.6–8.2), p < 0.001) and QaD = 1300–1000 mL/min (relative risk = 3.1 (95% confidence interval = 1.1–12.8), p = 0.031). The proportion of thromboses attributable to acute hypotension was 40% (95% confidence interval = 24–57). Conclusions: Our comparative study showed that an effective screening for graft stenosis and short-term thrombosis risk can rely on Qa surveillance alone, and suggested that avoiding acute hypotension and correcting stenosis at QaU < 1000 mL/min or QaD < 1300 mL/min can contain thrombosis risk.